Changes in mechanical properties of sprinting during repeated sprint in elite rugby sevens athletes. Issue 5 (28th May 2019) - Jiménez-Reyes, Pedro; Cross, Matt; Ross, Alex; Samozino, Pierre; Brughelli, Matt; Gill, Nicholas; Morin, Jean-Benoît
Abstract: This study aimed to analyse fatigue-induced changes in mechanical sprinting properties during a specific repeated-sprint test in elite rugby sevens athletes. Twenty elite rugby sevens players performed ten 40 m sprints on a 30 s cycle with participant's running back and forth in a marked lane. Radar was used to assess maximal overground sprint performance over each 40 m. Macroscopic mechanical properties (maximal horizontal force ( F 0 ), maximal horizontal power ( P max ), maximal ratio of horizontal force (RFpeak ), decrease in the ratio of horizontal-to-total force (DRF ), total force and maximal sprinting velocity ( v 0 )) were drawn from horizontal force velocity relationships, using a validated method applied to the speed–time data. Fatigue-induced changes were analysed comparing the first sprint to an average of 2 nd -4 th, 5 th -7 th and 8 th -10 th . Repeated-sprint ability (RSA) testing induced substantial changes in the maximal velocity component, with a decrease (–15%) in v 0 (effect size (ES) = –2.46 to –4.98), and to a lower extent (–5.9%) in the maximal force component F 0 (ES = –0.59). D RF moderately decreased (14%; ES=–0.76–1.11), and RFpeak largely decreased in the later sprints (ES = –0.32 to –1.27). Fatigue observed in this RSA test appeared to have a greater effect on the technical ability to produce horizontal force at high velocities, likely due to an alteration in the ability to maintain horizontally oriented force application when velocity increases rather than during the initial acceleration phase, but also the overall force production capacity. The ability to maintain forward-oriented force at high velocities is of central importance for identifying fatigue and monitoring load.